The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0102-86502008000300014
|View full text |Cite
|
Sign up to set email alerts
|

Ileostomy or colostomy for temporary decompression of colorectal anastomosis: systematic review and meta-analysis

Abstract: Purpose:The controversy regarding whether loop ileostomy or loop transverse colostomy is a better method for temporary decompression of colorectal anastomosis motivated this review. Methods: Five randomized trials were included, with 334 patients: 168 in the loop ileostomy group and 166 in the loop transverse colostomy group. The outcomes analyzed were: 1. Mortality; 2. Wound infection; 3. Time of stoma formation; 4. Time of stoma closure; 5. Time interval between stoma formation and closure; 6. Stoma prolapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…Endoluminal pressure at the anastomotic site has been reported to be associated with anastomotic leakage [31] and can be an important factor in the prevention of anastomotic leakage after rectal surgery. The proximal diversion, by means of either a colostomy or an ileostomy, minimizes the consequences of anastomotic leakage by preventing fecal flow through the anastomosis [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Endoluminal pressure at the anastomotic site has been reported to be associated with anastomotic leakage [31] and can be an important factor in the prevention of anastomotic leakage after rectal surgery. The proximal diversion, by means of either a colostomy or an ileostomy, minimizes the consequences of anastomotic leakage by preventing fecal flow through the anastomosis [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…There is no conclusive study in the literature about the superiority of colostomy or protective ileostomy after transit reconstruction surgery …”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the use of a stapler is not superior to the handsewn technique. Moreover the ileostomy technique looks to be the best choice for colorectal anastomoses decompression 4,5,6 . Further research on these surgical issues must be undertaken in order to obtain answers that are more definitive.…”
Section: Surgical Practice -Is It Evidence-based?mentioning
confidence: 99%
“…As a result a lot of good scientific evidence has been accumulated, particularly in colorectal surgery. Research questions such as the need for preoperative mechanical bowel preparation, pain control by means of epidural analgesia, time interval until starting postoperative administration of oral fluids and food, choice of surgical technique in colorectal anastomoses, use of drains and use of a nasogastric tube after elective laparotomy have been adressed 1,2,3,4,5,6,7 . Most of these studies are Cochrane reviews focusing on important healthcare interventions with particular emphasis given to surgical practice.…”
mentioning
confidence: 99%